Health-related qualify of life, angina type and coronary artery disease in patients with stable chest pain - Rieckmann, Nina; Neumann, Konrad; Feger, Sarah; Ibes, Paolo; Napp, Adriane; Preuß, Daniel; Dreger, Henryk; Feuchtner, Gudrun; Plank, Fabian; Suchánek, Vojtěch; Veselka, Josef; Engstrøm, Thomas; et al. (Health and quality of life outcomes, 2020)
BACKGROUND: Health-related quality of life (HRQoL) is impaired in patients with stable angina but patients often present with other forms of chest pain. The aim of this study was to compare the pre-diagnostic HRQoL in patients with suspected coronary artery disease (CAD) according to angina type, gender, and presence of obstructive CAD. METHODS: From the pilot study for the European DISCHARGE trial, we analysed data from 24 sites including 1263 patients (45.9% women, 61.1 ± 11.3 years) who were clinically referred for invasive coronary angiography (ICA; 617 patients) or coronary computed tomography angiography (CTA; 646 patients). Prior to the procedures, patients completed HRQoL questionnaires: the Short Form (SF)-12v2, the EuroQoL (EQ-5D-3 L) and the Hospital Anxiety and Depression Scale. RESULTS: Fifty-five percent of ICA and 35% of CTA patients had typical angina, 23 and 33% had atypical angina, 18 and 28% had non-anginal chest discomfort and 5 and 5% had other chest discomfort, respectively. Patients with typical angina had the poorest physical functioning compared to the other angina groups (SF-12 physical component score; 41.2 ± 8.8, 43.3 ± 9.1, 46.2 ± 9.0, 46.4 ± 11.4, respectively, all age and gender-adjusted p < 0.01), and highest anxiety levels (8.3 ± 4.1, 7.5 ± 4.1, 6.5 ± 4.0, 4.7 ± 4.5, respectively, all adjusted p < 0.01). On all other measures, patients with typical or atypical angina had lower HRQoL compared to the two other groups (all adjusted p < 0.05). HRQoL did not differ between patients with and without obstructive CAD while women had worse HRQoL compared with men, irrespective of age and angina type. CONCLUSIONS: Prior to a diagnostic procedure for stable chest pain, HRQoL is associated with chest pain characteristics, but not with obstructive CAD, and is significantly lower in women. TRIAL REGISTRATION: Clinicaltrials.gov, NCT02400229.
Keywords: Male; kvalita života; Coronary Artery Disease; Quality of Life; Health-related quality of life; Angina; Chest pain; pilotní projekty; rozložení podle pohlaví; Aged; mužské pohlaví; senioři; průzkumy a dotazníky; nemoci koronárních tepen; Sex Distribution; Coronary artery disease; Computed tomography angiography; lidé; Angina Pectoris; ženské pohlaví; Humans; angina pectoris; Invasive coronary angiography; Pilot Projects; Female; Surveys and Questionnaires; lidé středního věku; Middle Aged